KOREAN SIJO POEMS AND THEIR TRANSFORMATIONS - OH, Kyong-geun (International Journal of Korean Humanities and Social Sciences, 2016)
Sijo is an original genre of short Korean poems with a strictly defined structure reflecting the rhythm of a traditional Korean song. Sijo poems are the only traditional genre of Korean poetry, which is still practised by contemporary Korean poets. It gained tremendous popularity during the reign of the Joseon dynasty, especially among the Confucian scholars and noblemen who ruled the country. Sijo poetry has undergone a transformation as far as the topics and structure of sijo poems are concerned. Initially the authors of sijo belonged to the ruling class and were solely men (Confucian scholars). But with the passage of time and the development of society the representatives of the middle class started writing sijo poems as well. The sijo transformations also included the linguistic changes, which may be observed through the course of sijo history. The topics also changed as new types of sijo appeared beside traditional sijo devoted mainly to Confucian ideas formulated in a refined language.